Implementation and testing of a novel and customizable digital health platform and study on automatic medication dispensers in Iceland - María Kjartansdóttir 1991- (2023)
With an aging population, society might not have enough health care workers to care for those in need in the nearest future. Medication and the need for care will unavoidably increase as older adults often suffer from chronic diseases. Telehealth is proposed as a solution to the problem. Providing health care using ICT when the health care provider and the patient are at different locations is called telehealth. Telehealth is recognized as a way to make health care more effective. The thesis work is divided into two parts. In part one, 25 AMDs connected to a digital health platform were placed in the homes of 25 patients for seven months. Scores from questionnaires, electronic data events, and information from the employees were used to evaluate the benefits and possible negative aspects. Part two involved implementing, testing, and localizing the telemedicine functions of the digital health platform to provide telehealth services in Iceland. The study showed that all patients and their relatives were pleased with the AMD and 70% of the home care employees. The AMD is easy to use, even for a high age, as the mean age that finished the study was 79,1 (SD 9,1). The smart MDS saved both time and cost, reduced planned home visits, and, based on the event data, 24 minutes per patient were saved each day. Overall, the study indicated that a smart MDS system is beneficial and improves the quality of care. However, the technical issues that arose increased unplanned visits, and the time spent on administrating the system was more than expected. Guidelines for implementing telehealth solutions in the Icelandic health care setting are presented and can be used to make the process more manageable for implementing other solutions. The security audit revealed no serious comments, and the system is ready to be used in a pilot study. Getting the telehealth system ready for approval took over a year. Concluding that telehealth has great potential to make the health care system more efficient. However, getting telehealth ...